C-Reactive Protein (CRP): A poor prognostic biomarker in COVID-19 - Bouayed, Mohamed Zakaria; Laaribi, Ilyass; Chatar, Charaf Eddine Mohammed; Benaini, Iliass; Bouazzaoui, Mohammed Amine; Oujidi, Younes; Berrichi, Samia; El Aidouni, Ghizlane; Bkiyar, Houssam; Abda, Naima; Housni, Brahim (Frontiers in Immunology, 2022)
Introduction: The COVID-19 pandemic continues to be rampant with considerable morbidity and mortality worldwide since its emergence in December 2019. Several studies have focused on identifying different predictive factors of poor prognosis, including biological markers, such as C Reactive Protein among others. The objective of our work was to determine whether the CRP levels on admission to the intensive care unit are predictive of an unfavorable evolution of patients with COVID-19 through the experience of the Anesthesia and Intensive Care Unit of the University Hospital of Oujda and to compare our results with those reported in the literature. Methods: We conducted a retrospective, monocentric, descriptive and analytical study in the Department of Anesthesia and Intensive Care of the Mohammed VI University Hospital of Oujda, Morocco, between March 2020 and October 2021, including all critically ill patients admitted to the department during this period and meeting the inclusion criteria. The baseline admission CRP value was arbitrarily set at 100mg/d, thus conditioning the division of our patients into two groups (group 1: CRP < 100mg/d, group 2: CRP ≥ 100mg/d). Results: Among our 1035 included patients, 744 presented a CRP level equal or superior to 100mg/L, that is to say a percentage of 71.9% and 291 patients with a CRP<100mlg/L. Lung parenchymal involvement was more severe or even critical (CT involvement > 75%) in group 2 (60.8%) compared to group 1 (39.2%). In group 2, 79.8% of patients were mechanically ventilated, compared to 20.2% of patients in group 1. Finally, the mortality rate in patients with a CRP ≥ 100mg/l was 77.4%, compared with 22.6% for patients with a CRP < 100mg/l. These findings are all statistically highly significant (p<0.001) Conclusion: Given the high contagiousness of the virus and the emergence of several variants, the management of the COVID-19 pandemic has focused more on prevention through vaccination against the virus, but also on an early identification of patients likely to evolve unfavorably for a personalized management.